(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To compare the antihypotensive prevention of continuous intravenous infusion of noradrenaline with phenylephrine in the spinal block for cesarean section. Subjects and research methods: Pregnant women with indications for cesarean section at the National Hospital of Obstetrics and Gynecology in 2022. Results: Mean age, mean height, and mean weight in the study of the two groups were similar. All pregnant women in both groups showed loss of sensation at T10 (group N: 2.75 ± 0.71, group P: 2.67 ± 0.85) and T6 (group N: 4.17 ± 0.81, group P: 4.22 ± 0.89) relatively quickly, but the difference was not statistically significant with p>0.05. There was no difference in the time of motor inhibition according to the average Bromage score (p>0.05). The blood pressure rate drops 20% - 30%: 2 cases in group N (6%) and group P 4 cases (8%). Conclusion: Continuous intravenous infusion of noradrenaline was comparable with continuous intravenous infusion of phenylephrine in spinal anesthesia for cesarean section.